Assessment of Concentrations of Heavy Metals in Postmyocardial Infarction Patients and Patients Free from Cardiovascular Event. (31st January 2021) - Nowicki, Grzegorz Józef; Ślusarska, Barbara; Prystupa, Andrzej; Blicharska, Eliza; Adamczuk, Agnieszka; Czernecki, Tomasz; Jankowski, Krzysztof Jacek
Abstract : Cardiovascular diseases (CVDs) constitute the first cause of death among the population of developing and developed countries. Atherosclerosis, which is a disorder with multifactorial etiopathogenesis, underlies most CVDs. The available literature includes ample research studies on the influence of classic cardiovascular (CV) risk factors. However, environmental exposure to heavy metals, among other substances, is still an unappreciated risk factor of CVDs. This study aimed to assess the concentration of some heavy metals (copper (Cu), zinc (Zn), manganese (Mn), cobalt (Co), and iron (Fe)) in the blood serum of postmyocardial infarction (post-MI) patients and patients free from myocardial infarction (MI) as well as estimate the relationship between the occurrence of MI and increased concentration of heavy metals. The concentration of heavy metals (Cu, Zn, Mn, Co, and Fe) was assessed using the inductively coupled plasma mass spectrometry technique in a group of 146 respondents divided into two groups: post-MI group (study group (SG), n  = 74) and group without cardiovascular event (CVE) having a low CV risk (control group (CG), n  = 72). The concentration of the analyzed heavy metals was higher in SG. All the heavy metals showed a significant diagnostic value p < 0.001 . The highest value of area under the curve (AUC) was observed for manganese (Mn) (0.955; 95% confidence interval (CI) = 0.922–0.988), while the lowest value was found for zinc (Zn) (0.691; 95% CI = 0.599–0.782). In one-dimensional models, high concentrations of each of the analyzed heavy metals significantly increased the chances of having MI from 7-fold (Cu) to 128-fold (Mn). All the models containing a particular metal showed a significant and high discrimination value for MI occurrence (AUC 0.72–0.92). Higher concentrations of Cu, Zn, Mn, Co, and Fe were found to considerably increase the chances of having MI. Considering the increasingly higher environmental exposure to heavy metals in recent times, their concentrations can be distinguished as a potential risk factor of CVDs.